Creating a Vision for a Healthier Workforce Using a Systems-Based Approach. (September 2022) - Walkner, Laurie; May, Kathleen; Goldman, Bailey; Shultz, Hannah; Armbruster, Sonja; Grimm, Brandon; Hawley, Suzanne; Menke, Abigail; Orr, Shirley; Wilson, Kristin; Moody, Jeneane; Uden-Holman, Tanya; et al.
Abstract : Context: The public health system faces unprecedented challenges due to the pandemic, racism, health inequity, and the politicization of public health. At all levels of the system, the workforce is experiencing distress, burnout, safety issues, and attrition. Public health is being challenged to demonstrate and justify its impact and value, while also leveraging opportunities for learning and system strengthening. Program: To explore the current state and identify opportunities to strengthen the public health system, the Region 7 Midwestern Public Health Training Center (MPHTC), with support from Engaging Inquiry, embarked on a distinctive type of systems analysis, called "dynamic systems mapping." Implementation: This approach brought together diverse sectors of public health partners in the region to develop a rich contextual narrative and system-level understanding to highlight and align existing and emergent strengths, areas for growth, and tangible goals for the immediate- and long-term sustainability of local and regional health. Evaluation: Focus groups and workshops were conducted with diverse practitioners to identify upstream causes and downstream effects of 11 key forces driving system behavior. These focus groups resulted in the development of a visual map that MPHTC is utilizing to identify opportunities for leverage, develop strategies to maximize the potential impact of these leverage points, as well as facilitate continuous learning. Discussion: Public health utilization of systems mapping is a valuable approach to strengthening local and national system responses to current and future public health needs. Outcomes and lessons learned from the systems mapping process are discussed.